INTERPRETATIONS OF NAFKAH, GENDER RELATIONS, AND MOTIVATIONS FOR DIVORCE: A CASE STUDY OF DIVORCE LAWSUITS AT THE KEDIRI CITY RELIGIOUS COURT - Na'mah, Ulin; Rachmatulloh, Mochamamd Agus (istinbath, 2024)
The phenomenon of high divorce in Indonesian religious courts or Muslim communities causes government anxiety and raises cynical public opinion. Economic considerations are frequently referred to as the excuse for the wife's lawsuit. Data from the Kediri City Religious Court shows that there is a tendency for wives to file for divorce first. Not without justification, it is frequently prompted by the husband's perceived inability to satisfy the wife's requirements. The use of nafkah reasons in divorce can reveal that there is a contradictory tendency; on the one hand, women tend to charge a nafkah to men, and on the other hand, there is a tendency not to charge a nafkah to men or are willing to work to make ends meet. Divorce may not be a factor in limited economic conditions, but the perception of nafkah obligations imposed on husbands. It is critical to recognize that attempts to avoid divorce cannot be based just on economic empowerment but rather on cultural and religious ideas on partnerships and the separation of husband and wife roles. , this article examines the relationship between a contested divorce and economic conditions and perceptions of gender relations in the family, especially in earning a nafkah, to clarify this contradiction. Using a phenomenological approach. The economic reasons that have led wives to divorce are solely due to emptiness and even an emotional drought of love between husbands' wives. The indulgence of husband and wife in dividing household roles from transitional to egalitarian ideology also requires attention and respect for each other.